Does prior message work to promote motivation for serious game playing? - Park, Eun Hae (Kansas State University, 2011)
This study aims to investigate effects of external aid that can enhance motivation and performance of serious game playing to maximize learning effects. Based on self-determination theory, two types of rationales, intrinsic goal framing and extrinsic goal framing, were examined to know which message type is effective. Also, individual’s level of issue involvement was tested as a moderating variable. To investigate the effects of goal framing on motivation and moderating effects of involvement, this study designed a 2x2 (goal framing x involvement) between subjects with 120 middle school students in Korea. Three procedures involved for the experiment: 1) receiving message for manipulating involvement and goal framing 2) Playing actual serious game, and 3) answering survey questionnaire. Overall, providing intrinsic goal before a serious game was more effective to increase both motivation and performance than presenting extrinsic goal. However, there was no main effects and interaction effect in terms of issue involvement.
Keywords: Serious game; Motivation; Journalism (0391)